Syntheses and chemical properties of β-nicotinamide riboside and its analogues and derivatives - Makarov, Mikhail V.; Migaud, Marie E. (Beilstein Journal of Organic Chemistry, 2019)
The β-anomeric form of nicotinamide riboside (NR+) is a precursor for nicotinamide adenine dinucleotide (NAD+), a redox cofactor playing a critical role in cell metabolism. Recently, it has been demonstrated that its chloride salt (NR+Cl−) has beneficial effects, and now NR+Cl− is available as a dietary supplement. Syntheses and studies of analogues and derivatives of NR+ are of high importance to unravel the role of NR+ in biochemical processes in living cells and to elaborate the next generation of NR+ derivatives and conjugates with the view of developing novel drug and food supplement candidates. This review provides an overview of the synthetic approaches, the chemical properties, and the structural and functional modifications which have been undertaken on the nicotinoyl riboside scaffold.
Keywords: anomers; glycosylation; isotopologues; isotopomeres; nicotinamide riboside